Edward McPherson papers - McPherson, Edward, 1830-1895.; McCreary, Robert G., -1883.; United States. Congress. House. Office of the Clerk
Correspondence, speeches, writings, notes, financial papers, family papers, family history, genealogical material, and other papers relating to McPherson's career in the House of Representatives as legislator and clerk of the House, and to Republican Party politics and campaigns nationally and in Pennsylvania during Reconstruction. Includes papers relating to the McPherson family in central Pennsylvania; records (1856-1888) of the Office of the Clerk, U.S. House of Representatives; estate papers of Thaddeus Stevens and material collected for his biography; records of the Presbyterian Church, Marsh Creek, Pa.; and correspondence, law office files, and legal documents of Robert G. McCreary, of Gettysburg, Pa. Subjects include history of Pennsylvania, especially Gettysburg and Adams Co., Pa.; education in frontier Pennsylvania; property investments in Pennsylvania; administration of the Gettysburg and Black's Tavern Turnpike Road; military services; and the tariff.
Family members represented include Janet McPherson, John Bayard McPherson, Robert McPherson, William McPherson, and Robert M'Pherson.
Correspondents include James Gillespie Blaine, Noah Brooks, William E. Chandler, George William Childs, James A. Garfield, and E.B. Washburne.
Editor, statistician, and U.S. representative from Pennsylvania.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Brooks, Noah, -- 1830-1903 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Childs, George William, -- 1829-1894 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; McPherson, Janet, -- 1689-1767.; McPherson, John Bayard, -- 1789-1858.; McPherson, Robert, -- 1689-1749.; M'Pherson, Robert, -- 1730-1789.; McPherson, William, -- 1757-1832.; Stevens, Thaddeus, -- 1792-1868.; Stevens, Thaddeus, -- 1792-1868 -- Estate; Washburne, E. B. -- 1816-1887 -- Correspondence; McPherson family; United States. -- Congress. -- House; Republican Party (U.S. : 1854- ); Education -- Pennsylvania; Frontier and pioneer life -- Pennsylvania; Genealogy; Political campaigns -- Pennsylvania; Political campaigns -- United States; Practice of law -- Pennsylvania -- Gettysburg; Presbyterian Church -- Pennsylvania -- Marsh Creek; Real estate investment; Reconstruction (U.S. history, 1865-1877); Tariff -- United States; Toll roads -- Pennsylvania; Adams County (Pa.) -- History; Gettysburg County (Pa.) -- History; Pennsylvania -- History; Pennsylvania -- Politics and government; Pennsylvania -- Social life and customs; United States -- Politics and government -- 1865-1900.; Gettysburg and Black's Tavern Turnpike Road (Pa.); Editors; Representatives, U.S. Congress -- Pennsylvania; Statisticians